THE PLACE OF WOMEN IN THE NEIGHBORHOOD AT THE MOMENT - Karamov Mamasharif Jamilovich (American Journals, 2024)
This article provides information about the reforms that are being carried out to increase the role of women in the neighborhood and the social and political activity of women in the life of society.
Keywords: Neighborhood, society, family, women, jobs, social protection.